2009
DOI: 10.1007/s11325-009-0259-1
|View full text |Cite
|
Sign up to set email alerts
|

Pro-atherogenic cytokine profile of patients with suspected obstructive sleep apnea

Abstract: We did not find significant associations between OSA and markers of activated innate immunity (IL-1B, 6, and 8). However, OSA severity was independently associated with serum levels of sVCAM-1 and leptin; these may represent mechanisms involved in the pathogenesis of OSA-related CVD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 25 publications
1
18
0
Order By: Relevance
“…In OSAS patients, several inflammatory factors can be found in high concentrations, which can be used as biological markers [32], such as interleukin-6 (IL-6) [33], interleukin-8 (IL-8) [34,35], tumor necrosis factor-α (TNF-α) [35], vascular endothelial growth factor (VEGF) [36], leptine [37,38], and C-reactive protein (CRP) [39,40].…”
Section: Inflammatory Markersmentioning
confidence: 99%
“…In OSAS patients, several inflammatory factors can be found in high concentrations, which can be used as biological markers [32], such as interleukin-6 (IL-6) [33], interleukin-8 (IL-8) [34,35], tumor necrosis factor-α (TNF-α) [35], vascular endothelial growth factor (VEGF) [36], leptine [37,38], and C-reactive protein (CRP) [39,40].…”
Section: Inflammatory Markersmentioning
confidence: 99%
“…The levels of the pro-inflammatory cytokine TNF-α are correlated with the severity of OSAS. TNF-α modulates physiological sleep [88] [97][98][99]. Nevertheless, Zhang and co-workers have recently showed that genetic variants of the IL-6 gene confer different susceptibility to develop OSAS, thus suggesting a potential approach to assess the risk for OSAS [100].…”
Section: Systemic Inflammatory Mediatorsmentioning
confidence: 99%
“…The presence of systemic inflammation in OSAS is supported by elevated levels of circulating inflammatory markers including C-reactive protein, interleukin-6 (IL-6), IL-8, and tumor necrosis factor-α (TNF-α). 4 Several studies have verified the presence of inflammation in the nasal mucosa, uvula, soft palate, and pharyngolaryngeal tract of OSAS patients, which indicates that upper airway inflammation is correlated with OSAS. 10,11 Furthermore, there is clinical 13 and pneumonia.…”
Section: Discussionmentioning
confidence: 96%